2018
DOI: 10.1098/rstb.2017.0289
|View full text |Cite
|
Sign up to set email alerts
|

The impact of environmental interventions among mouse siblings on the heritability and malleability of general cognitive ability

Abstract: General cognitive ability can be highly heritable in some species, but at the same time, is very malleable. This apparent paradox could potentially be explained by gene-environment interactions and correlations that remain hidden due to experimental limitations on human research and blind spots in animal research. Here, we shed light on this issue by combining the design of a sibling study with an environmental intervention administered to laboratory mice. The analysis included 58 litters of four full-sibling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
41
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 42 publications
2
41
1
Order By: Relevance
“…Moreover, several experimental studies have shown that artificial selection for cognitive traits or brain size can drive directional changes across generations [56 -59]. However, understanding the heritability of cognitive performance (and its evolutionary consequences; see below) is far from straightforward, as discussed by two papers in this special issue [8,9]. As heritability is assessed by partitioning variance between environmental and genetic components, heritability estimates are highly dependent on the local environment.…”
Section: (B) Heritabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, several experimental studies have shown that artificial selection for cognitive traits or brain size can drive directional changes across generations [56 -59]. However, understanding the heritability of cognitive performance (and its evolutionary consequences; see below) is far from straightforward, as discussed by two papers in this special issue [8,9]. As heritability is assessed by partitioning variance between environmental and genetic components, heritability estimates are highly dependent on the local environment.…”
Section: (B) Heritabilitymentioning
confidence: 99%
“…As heritability is assessed by partitioning variance between environmental and genetic components, heritability estimates are highly dependent on the local environment. For example, Sauce et al [8] show strong heritability of cognitive performance in mice raised in standard laboratory conditions, while in groups of mice exposed to environmental enrichment, the increased environmental variance component leads to heritability estimates of effectively zero. Heritability estimates may also be highly specific to particular cognitive traits.…”
Section: (B) Heritabilitymentioning
confidence: 99%
“…We have to understand the causes and consequences of intra-individual variation in cognitive performance to understand how natural selection shapes cognition (Boogert et al 2018). A recent study found that cognitive ability is heritable in mice, but also highly malleable according to environmental effects (Sauce et al 2018). Intra-individual variation in cognitive performance is thus possibly the result of constant interaction between genes and experience that may be mediated by epigenetic mechanisms (Sweatt 2019).…”
Section: The Role Of Dna and Histone Modifications In The Brain And Cmentioning
confidence: 99%
“…Alternatively, brothers might not necessarily copy each other's songs directly, but show similar song learning tendencies (e.g. they may, genetically and/or through early-life effects, be predisposed to attend to the same cues in their (social) environment, as seen in mouse sibs [ 64 ]), resulting in more similar songs indirectly. It is impossible to distinguish between these hypotheses without further experimental manipulation.…”
Section: Discussionmentioning
confidence: 99%